Viewing benefit sharing in global health research through the lens of Aristotelian justice - Dauda, Bege (Journal of medical ethics, 2017)
The ethics of benefit sharing has been a topical issue in global health research in resource-limited countries. It pertains to the distribution of goods, benefits and advantages to the research participants, communities and countries that are involved in research. One of the nuances in benefit sharing is the ethical justification on which the concept should be based. Extensive literature outlining the different principles underlying benefit sharing is available. The purpose of this paper is to examine the proposed principles using Aristotelian principles of justice. The paper assesses the central idea of Aristotelian justice and applies and evaluates this idea to benefit sharing in research, especially when commercial research sponsors conduct research in resource-limited countries. Two categories of Aristotelian justice—universal and particular—were examined and their contribution to the benefit-sharing discourse assessed. On the one hand, benefit sharing in accordance with universal justice requires that for-profit research sponsors obey the legal regulations and international standards set for benefit sharing. On the other hand, benefit sharing in accordance with particular justice transcends obeying legal requirements and standards to a realm of acting in an ethically accepted manner. Accordingly, the paper further examines three perspectives of particular justice and develops ethical justification for benefit sharing in global health research. As Aristotelian justice is still relevant to the contemporary discourse on justice, this paper broadens the ethical justifications of benefit sharing in global health research.